2013
DOI: 10.3109/07388551.2013.790874
|View full text |Cite
|
Sign up to set email alerts
|

Chitinases: in agriculture and human healthcare

Abstract: Biological control of phytopathogenic fungi and insects continues to inspire the research and development of environmentally friendly bioactive alternatives. Potentially lytic enzymes, chitinases can act as a biocontrol agent against agriculturally important fungi and insects. The cell wall in fungi and protective covers, i.e. cuticle in insects shares a key structural polymer, chitin, a β-1,4-linked N-acetylglucosamine polymer. Therefore, it is advantageous to develop a common biocontrol agent against both of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 242 publications
1
51
0
4
Order By: Relevance
“…5) on the catalytic and chitin binding domains of HCHT. The results showed that GH18-containing genes are found in genomes of all domains of life and that this ancestral family of catalytic domains is present in numerous modular enzymes involved in various biological processes 20, 3133 . It is therefore not surprising that they are associated to a wide variety of domains as it is illustrated by the 377 different architectures classified in Pfam database (http://pfam.xfam.org).…”
Section: Discussionmentioning
confidence: 99%
“…5) on the catalytic and chitin binding domains of HCHT. The results showed that GH18-containing genes are found in genomes of all domains of life and that this ancestral family of catalytic domains is present in numerous modular enzymes involved in various biological processes 20, 3133 . It is therefore not surprising that they are associated to a wide variety of domains as it is illustrated by the 377 different architectures classified in Pfam database (http://pfam.xfam.org).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Streptomyces sp. (Gram-positive, filamentous bacteria) has attracted more attention among researchers because of their ability to suppress growth of a wide variety of phytopathogenic fungi [12,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Endokitinase memotong polimer kitin secara acak dan menghasilkan dimer, trimer, tetramer, dan oligomer gula. N-asetil-glukosaminidase yang memutuskan diasetilkitobiosa dan menghasilkan NAG (Dahiya et al, 2006;Herdyastuti et al, 2009 (Nagpure et al, 2014).…”
Section: Screening and Chitinolytic Activity Evaluation Of Nine Indigunclassified